Chapter Polyphonic Music of the Fourteenth Century in Aragon: Reassessing a Panorama of Fragmentary Sources - Catalunya, David (Studies in Manuscript Cultures, 2020)
Fragments of music manuscripts are some of the commonest finds inside bindings of later volumes, or unlabeled boxes tucked away in libraries and archives. Their surviving radically shaped our modern understanding of early European music. This volume looks at 'disiecta membra' not as relics of a lost whole, but as principal objects of study, illuminating societal, material, and cultural contexts, and requiring specific approaches and methodologies.